Chemical profile of xanthine oxidase inhibitor fraction of Persicaria hydropiper - Noor Hashim, Noor Haslinda; Maulidiani, M.; Mediani, Ahmed; Abas, Faridah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Persicaria hydropiper, locally known as kesum, is an herb belongs to the family Polygonaceae. It has been used widely in many countries as food flavoring and possesses a wide range of medicinal values. The total phenolic content and xanthine oxidase inhibitory activity of the methanolic extract of P. hydropiper and fractions were determined spectrophotometrically. The butanol fraction was found to contain high phenolic content and was able to inhibit xanthine oxidase activity. Online profiling using liquid chromatography coupled with electrospray ionisation spectrometry (LC-ESIMS/MS) has revealed ten constituents in this active fraction. The major components were flavonoid derivatives and flavonoid sulphates, which were confirmed by comparison with an authentic standards as well as their MS/MS fragmentation patterns and UV spectra.